PROFIL SWAMEDIKASI ANALGETIK PADA MAHASISWA POLITEKNIK INDONUSA SURAKARTA - Siti Ma'rufah; Khusnul khotimah; Aptika Oktaviana Trisna Dewi; Riyan Setiyanto (Jurnal Farmasindo, 2020)
Self-medication is a community effort to treat symptoms without a doctor's prescription. With self-medication, complaints can be resolved and resolved quickly and effectively. Medicines that are sold freely in kiosks make it easier for people to get drugs to carry out self-medicated actions. The purpose of this study was to determine the profile of using analgesic drugs by self-medication in students of Polytechnic Indonusa Surakarta. This research is a cross sectional approach. Data collection using a questionnaire via google form to 88 respondents. The sampling technique used is random sampling by taking sample members randomly. Quantitative data processing uses Microsoft Office Excel.The results showed that the characteristics of the respondents who participated in this study were mostly women aged 17-25 years from 5 study programs, namely D3 Pharmacy, D3 Mass Communication, D3 Hospitality, D3 Information Management and D3 Automotive Machinery. The most pain complaints experienced by respondents were headache, toothache and menstrual pain. Respondents tended to use 1 type of synthetic drug or traditional / herbal medicine with only 1 type of active ingredient composition and more often mentioned the generic name of the drug when buying the drug. Respondents preferred paracetamol to deal with pain complaints. The place of purchase of self-medicated drugs is more dominant in pharmacies. Most of the reasons for doing self-medication were because of the experience of recovering with the same medicine and the perception that the disease was mild.